Dataset for the life cycle assessment of the high speed rail network in Spain - Kortazar, Andoni; Bueno, Gorka; Hoyos, David (Data in brief, 2021)
A life cycle assessment (LCA) of the Spanish high speed rail (HSR) network in service in 2016 (2583 km) was conducted. Life cycle inventory (LCI) data related to the construction and maintenance phases of the infrastructure was collected using Google Earth tool, and complemented with data obtained from the LCA carried out by Tuchschmid et al. [1]. LCI data associated with the operation phase of the infrastructure was built on available fragmentary data on passenger movements for the year 2016 [2–4], processed with a python algorithm to estimate the transport service provided by the infrastructure. Environmental impacts for transport modes were obtained from Ecoinvent v3.7 database [5,6] and processed with openLCA software [7]. Life cycle impact assessment (LCIA) results gathered in the dataset include Global Warming (GWP100a), Cumulative Energy Demand and total emissions for PM10, SO2, NOX and NMVOC. This dataset presents a detailed description of the Spanish HSR network, including the length of each item (bridges, tunnels, earthworks, railway tracks), and a robust estimation of passenger transport over the infrastructure for year 2016. The LCI data presented in this paper support the original research done on whether the construction of Spanish HSR network infrastructure is justified in terms of reducing environmental impacts and energy consumption [8], and may be used as a baseline for future studies on transport economics.